Saying 'yes' or 'no' to short-term holiday letting in stratified properties in Malaysia - Mohamad, Nor Asiah (Universiti Malaysia Sarawak, 2020)
This paper determines the legal position of short-term holiday letting involving strata properties. Strata properties are unique where the owners share the common properties and have a say in the management of the properties. Short-term letting is also exciting where it involves online transaction. The current sharing economy trend received mixed views in various jurisdictions and it is still new in Malaysia. This paper adopts content analysis approach where documents, policies and laws related to short-term letting and stratified properties will be analysed. This research seeks to determine whether there are legal and social issues related to short-term letting in Malaysia. A case study on Airbnb is also discussed to gauge the seriousness of the issue. Malaysia has no specific law dealing with short-term letting especially involving stratified properties. Other jurisdictions such as New South Wales, Australia provides laws relating to the requirement to inform the Owner's Corporation of any lease or sublease of strata unit, overcrowding policy as well as review of Bylaws towards protecting the rights and interests of the owner. Strata properties laws in Malaysia lags behind thus short-term holiday letting provisions are much to be desired. Studies are needed to determine the actual impact of short term letting for strata living including any economic benefit arising from short-term accommodation sector or does it cause encroachment to the rights of the owners living in the strata scheme.